2009
DOI: 10.1016/j.bcp.2009.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acetylcholine receptors and the ascending dopamine pathways

Abstract: Nicotinic acetylcholine receptors (nAChRs) are widely expressed in midbrain dopamine neurons that project to dorsal striatum, nucleus accumbens and prefrontal cortex. Thus nAChRs can influence the functions of these three pathways; notably motor control, 'reward' and executive function, respectively. Diverse subtypes of nAChRs have been identified on dopamine cell bodies and terminals as well as on neighbouring afferents and interneurons. Here we review the molecular and cellular mechanisms through which nAChR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 157 publications
2
114
0
1
Order By: Relevance
“…The present study also suggests that D1R ligands do not affect action potential dependent dopamine release. However, it must be considered if single or multiple nAChR subtypes play this essential and complex role in the bidirectional effect of nicotine on dopamine release [24]. Besides desensitization of the β2-containing nAChR, it has been suggested that there is an important role for functional α7*nAChRs [25] and this may depend upon endogenous ACh levels evoked by the stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also suggests that D1R ligands do not affect action potential dependent dopamine release. However, it must be considered if single or multiple nAChR subtypes play this essential and complex role in the bidirectional effect of nicotine on dopamine release [24]. Besides desensitization of the β2-containing nAChR, it has been suggested that there is an important role for functional α7*nAChRs [25] and this may depend upon endogenous ACh levels evoked by the stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Aligning pharmacological actions for a range of PAMs (literature and current study) with their proposed binding sites, it appears that binding in ECD interfaces mostly result in agonist CRR left shifts, whereas TMD binding can further result in increased agonist-evoked peak currents, delayed desensitization characteristics, and direct agonist independent receptor activation. 7,8,9-tetrahydro-1H-benzo[g]indole-5-sulfonamide (NS206) was synthesized at NeuroSearch A/S according to methods described in patent WO 01/55110. 3-(3-(Pyridine-3-yl)-1,2,4-oxadiazol-5-yl)benzonitrile (NS9283) was likewise synthesized at NeuroSearch A/S as described by Timmermann et al (9).…”
mentioning
confidence: 99%
“…A remarkable diversity of b2* nAChR subtypes modulates DA release in these projections Gotti et al, 2009;Livingstone and Wonnacott, 2009). These projections, in particular those to the NAc and ventral striatum, are likely involved in reward pathways and the reinforcing properties of nicotine contributing to addiction.…”
Section: Nicotinementioning
confidence: 99%
“…This burst firing is thought to be mediated by activation of NMDARs on DAergic cell bodies by glutamatergic afferents from the PFC (Chergui et al, 1993;Tong et al, 1996). It is proposed that stimulation of presynaptic a7 nAChRs on glutamatergic afferents (Jones and Wonnacott, 2004) releases glutamate activating NMDARs on DAergic cell bodies to produce the burst firing (Livingstone and Wonnacott, 2009). The activation of NMDARs not only induces acute changes in firing but can induce long-lasting presynaptic facilitation and postsynaptic NMDAR-dependent LTP, resulting in sustained increases in the sensitivity of the DAergic neurons to burst firing (Mansvelder and McGehee, 2000;Mansvelder et al, 2002).…”
Section: Nicotinementioning
confidence: 99%